Relativistic Hartree Bogoliubov model with Density Dependent meson-nucleon couplings - Lalazissis, G. A.; Niksic, T.; Vretenar, D.; Ring, P. (HNPS Advances in Nuclear Physics, 2020)
A new improved relativistic mean-field effective interaction with explicit density dependence of the meson-nucleon couplings is proposed. The new effective interaction is called DD-ME2 and it is tested in Relativistic Hartree-Bogoliubov (RHB) and RPA calculations of nuclear ground-states and properties of excited states.